Effect of spacing and fertilizer levels on yield, quality and nutrient uptake of fennel (Foeniculum vulgare Mill.) under northern dry zone of Karnataka: Effect of spacing and fertilizer levels on fennel - Rajeshwari, M; Vishwanath, Y C; Vijayakumar Narayanapur, B; Prabhakar, Itigi; Vijaymahantesh; Anita Ghandhe, R (Journal of Spices and Aromatic Crops, 2022)
An experiment was carried out on effect of spacing and fertilizer levels on yield, quality and nutrient uptake of fennel (Foeniculum vulgare Mill.) under northern dry zone of Karnataka. Among various spacing levels, 60 x 30 cm spacing recorded highest seed yield. The highest essential oil content and essential oil yield was obtained in 60 x 40 cm spacing. Nutrient uptake was found maximum in 60 x 30 cm spacing. The maximum seed yield, essential oil content, oil yield and total nutrient uptake was obtained by supplying 100:50:40 NPK kg ha-1 and it was at par with 90:40:30 N, P2O5, K2O kg ha-1 respectively.